Experimental and Theoretical Investigation of the Effect of Oxygen Vacancies on the Electronic Structure and Pseudocapacitance of MnO2. Issue 15 (3rd July 2019) - Yan, Lijin; Shen, Cheng; Niu, Lengyuan; Liu, Mao‐cheng; Lin, Jianhua; Chen, Taiqiang; Gong, Yinyan; Li, Can; Liu, Xinjuan; Xu, Shiqing
Abstract: Defect engineering is an effective way to modulate the intrinsic physicochemical properties of materials. In this work, δ‐MnO2 with oxygen vacancies is fabricated by a simple oxidation or reduction process, and the relationship between the electronic structure and pseudocapacitance is systematically studied through experimental analysis and theoretical calculations. The peaks in the Raman spectra of the as‐prepared samples are shifted compared with those of pure MnO2 and the Mn 3+ /Mn 4+ ratio and O species content also change after the introduction of oxygen vacancies. The optimized samples exhibit a better specific capacitance of 207 F g −1 after the oxidation process and 181.4 F g −1 after the reduction treatment compared with only 143.9 F g −1 for the pure MnO2 . The samples obtained through the oxidation or reduction process also retain 93.3 or 86.4 % of the initial capacity after 5000 cycles. The excellent properties are attributed to the enhanced conductivity and increased surface reactivity or electrochemically active sites. Theoretical calculations demonstrate that the presence of oxygen vacancies leads to an increase in the density of states, which improves the redox reaction of MnO2 . This study will provide a reference for exploring and designing highperformance pseudocapacitive materials. Abstract : (N)O vacancies ! δ‐MnO2 containing oxygen vacancies was fabricated by a simple oxidation or reduction process. The samples exhibited a better specific capacitance than pure δ‐MnO2 . The excellent properties were attributed to the enhanced conductivity and increased surface reactivity or electrochemically active sitesLengyuan Niu, Shiqing Xu et al. (China Jiliang University): Theoretical and experimental evidence that MnO2 with oxygen vacancies has better specific capacitance than pure MnO2.